Sejarah Bangsa Arab Pra Islam - Naldi, Danu Resfi (UIN Sunan Gunung Djati Bandung, 2023)
This research deals with an overview of the position, power, and socio-economic conditions of the Arabs from the 7th Century to the 21st Century. We explore the significant political, religious, social, economic and moral changes in the history of the Arabs, and describe the role of the major empires in the Arabian Peninsula. We draw on various historical references and academic research to support this analysis. The aim of this research is to investigate and understand a number of important aspects relating to the Arabs, in terms of historical, political, religious, social, economic, moral, and major empires in the Arabian Peninsula. More specific research objectives follow. The research method used is Secondary Data analysis, which identifies relevant secondary sources such as books, journal articles, research reports, and online sources that can provide information about the position of the Arab nation, its peoples, power, political conditions, religion, social, economic, morals, and kingdoms in the Arabian Peninsula. The result of this is to reveal more in-depth details about each of these aspects, including the historical events and cultural developments that contributed to the condition of the Arabian Peninsula before the arrival of Islam. Keywords: History, Arabs, Islam